カキ ノ ナンキョク ショウワキチ シュウヘン ノ テイチャクヒョウカ ニオケル クロロフィルa オヨビ ショウサンエン ノウド ノ ジカン ヘンカ - 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Fukuchi, Mitsuo (情報・システム研究機構 国立極地研究所, 2004)
P(論文) 1996年12月30日,1997年1月12日及び21日に,南極昭和基地周辺のリュツォ・ホルム湾の4点において,水深5mから海底の間の数層から海水試料を得た.得られた試料を基にクロロフィルa(Chl a)及び硝酸塩(NO3)濃度の鉛直分布を調べた.いずれの観測点においても表層の成層水中(<20m)でChl a及びNO3濃度が時間とともに大きく変化した.両濃度には有意な負の関係があった(n=40, P<0.01).この関係は,Chl aが1μg l-1増加するときNO3を0.89μM消費することを示唆する.しかしながら,本研究で見られたような厚い海氷(2.0-3.6m)下における光強度は,植物プランクトンが増殖するのに厳しい条件にある.本研究で観測されたChl aの増加が,植物プランクトンが厚い定着氷下で増殖した結果とは考えにくい.好光条件の下でChl aを増加させ,NO3を消費した海水が観測海域へ移流していたと考えられる.この移流が,厚い定着氷下で見かけ上Chl aが増加しNO3が低下する要因と思われる. Seawater samples beneath fast ice were collected from several depths using a Niskin bottle at four sites near Syowa Station, Antarctica, on 30 December 1996, and 12 and 21 January 1997. Vertical distributions of chlorophyll a (Chl a) and nitrate (NO3) concentrations were determined. Substantial temporal changes in Chl a and NO3 concentrations occurred in the surface stratified layer (<20m). There was a significant negative correlation between both the concentrations (n=40, P<0.01). This relationship suggests that an increase of 1μg l-1 of Chl a consumes 0.89μM of NO3 under fast ice. However, light limitation is severe for phytoplankton growing under thick sea ice (2.0-3.6m), as observed in the present study. It is unlikely that the observed increases of Chl a result from phytoplankton growth under heavy fast ice. Seawater, in which Chl a has increased and NO3 has been consumed under favorable light conditions, may be advected into the study area. This advection may be responsible for the apparent increase of Chl a and decrease of NO3 concentrations under the heavy fast ice. departmental bulletin paper